The NCAA's breaking point for equal opportunity: A Title IX perspective on name, image, and likeness sponsorship legislation. Issue 1 (2nd January 2022) - Sorbe, Josh; Custis, Tyler; Weinandt, Mandie
ABSTRACT: This paper analyzes the efficacy of Title IX in the context of name, image, and likeness (NIL) and NCAA Division I athletic department expenditures. The research examines Title IX's legislative history, current compliance rules, litigation in the courts, and a current literature review. Using publicly reported data to the US Department of Education, fixed effects models testing measure of participation and expenditure parity were explored. The results show that most NCAA Division 1 schools lack participation and expenditure parity, men's football has a large impact on both participation and spending, and disparities in expenditures are more distinct than participation. Ultimately, the market-based provisions allowing exceptions for inequitable gender expenditures have swallowed the rule: equality in sports. Given the limited population NIL legislation likely would benefit, this study emphasizes the need to take into account the values Title IX safeguards when revising policies impacting amateurism, athlete benefits, and gender equity.